Literature Study: Development of Case-Based Teaching Materials through North Sumatra Culture - Nurhayati, Nurhayati; Fathurrohman, Fathurrohman; Rosidah, Ulfa Khoirotul (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
This research aims to develop case-based teaching materials that integrate North Sumatran culture into Pancasila Education learning in elementary schools. The method used is qualitative research with a literature study approach, where data is collected from various sources such as books, proposals, articles, and scientific journals. The collected data is analyzed in depth and then presented in narrative form. The results of the study show that there is an increase in student activity and activeness in learning Pancasila Education after the application of this teaching material. In cycle I, students tend to be less active, but in cycle II, student activity increases and falls into the active category. Based on the results of the literature review, case-based teaching materials that elevate the culture of North Sumatra have been proven to make it easier for students to understand, foster interest in learning, and be effectively applied in elementary schools.